Penerapan Model Picture And Picture Berbantuan Media Flashcard Untuk Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas 2 Sekolah Dasar - Liana Wahyuningsih; Acep Ruswan; Sofyan Iskandar (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This classroom action research was motivated by students' lack of interest in reading so that students could not answer the questions to the fullest, especially in Indonesian language subjects which were caused by learning activities in the classroom that were not conducive. The purpose of this study was to determine the picture and picture model planning assisted by flash card media to improve the reading ability of students in grade 2 elementary schools, to find out student learning activities when using the picture and picture model assisted by flash card media in grade 2 elementary school students and to determine the increase in students' reading skills after using the picture and picture model assisted by flash card media in grade 2 students. elementary school. This research is a class action research with research subjects of class II students at SDN 2 Serang in Cirebon. The research instruments used in this study consisted of student activity observation sheets and learning outcomes evaluation tests. Through this method, teachers can introduce the concept of reading in an interesting and interactive way. In this model, interesting pictures are presented sequentially to form a narrative related to the written text. The use of flash card media provides visual clarity and stimulates students' imaginations, thus helping them understand text content better. The advantage of applying the Picture and Picture Model is that it creates a fun learning environment, encourages students' active participation, and increases their motivation and confidence in reading. By displaying pictures that are relevant to the text, students can develop cognitive skills and critical thinking. In addition, through flash card media, students can involve all senses in the learning process, increasing information retention and concept connection. The results of the research in the first cycle showed that the average acquisition of student learning activity was 73%, in the second cycle there was an increase with an average acquisition of student activity reaching 94%. The result of reading ability in cycle I was 36.3% and in cycle II it increased to 90.9%. With the data obtained from the results of this study, it can be concluded that the application of the picture and picture model assisted by flash card media to improve the beginning reading skills of grade 2 elementary school students can increase students' activity and reading ability. Keywords: Picture and Picture Model, Flash Card, Reading Ability, Elementary School.